How can public international law contribute to the maintenance of international peace and security? - Klein Eckart (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2023)
The article offers a comprehensive exploration of the complexities and nuances surrounding international peace and the legal mechanisms designed to achieve it. It delves into the historical evolution of public international law concerning war, peace, and international security. The article underscores the evolution of warfare as a means to achieve political objectives through sovereign rulers and states, leading to attempts at restraining warfare by humanitarian principles. It discusses the roles of the League of Nations, the Briand-Kellogg Pact, and the United Nations Charter in their attempts to curb the war. Despite peace being crucial for human rights and international behavior, wars persist. Consequently, the article scrutinizes the primary challenges associated with upholding global peace. Ultimately, it concludes that while public international law is pivotal in the pursuit of peace and justice, realizing these ideals necessitates the united determination of the collective will of all peoples to work towards that direction.